2016
DOI: 10.1089/cyber.2015.0623
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concept Clarity and Online Self-Presentation in Adolescents

Abstract: The Internet may be conceptualized as a social laboratory, providing freedom to experiment with different presentations of self. Adolescence is an important time in the development of self-concept; however, little is known about how clarity of self-concept relates to online behavior. The principal aim of this study was to test the hypothesis that self-concept clarity would be associated with adolescents' inclination to experiment with online self-presentation. One hundred forty-eight participants aged 13-18 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 24 publications
5
58
1
6
Order By: Relevance
“…Moreover, our results have shown that adolescents of our sample frequently underestimate the consequences of their activities in the web and in virtual communities, probably because of their difficulties in identifying the relationship between the real and the virtual identity, Our findings are consistent with recent observations by Fullwood, James and Chen-Wilson (2016), who highlighted that adolescents who have a poorly integrated identity and self-representation are more prone to manifest an idealized version of themselves in the Internet, while youths with a more stable (and therefore more self-aware) self-representation have a more coherent and unitary self-representation.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, our results have shown that adolescents of our sample frequently underestimate the consequences of their activities in the web and in virtual communities, probably because of their difficulties in identifying the relationship between the real and the virtual identity, Our findings are consistent with recent observations by Fullwood, James and Chen-Wilson (2016), who highlighted that adolescents who have a poorly integrated identity and self-representation are more prone to manifest an idealized version of themselves in the Internet, while youths with a more stable (and therefore more self-aware) self-representation have a more coherent and unitary self-representation.…”
Section: Resultssupporting
confidence: 93%
“…Perhaps this frequent use of online communication, and the associated positive results in peer relationships, may be due to the accessibility and asynchrony that characterises online media (Valkenburg & Peter, 2009). These features enhance the development of self-presentation and selfrevelation skills, which are necessary for the development of personal identity, intimacy and sexuality (Fullwood, James, & Chen-Wilson, 2016;Wang, Jackson, & Zhang, 2011). Furthermore, the association found between a greater use of online communication by text messages and no bullying at school was contrary to the study by Best et al (2014), which established cyberbullying as a risk factor of online communication, because a greater use of the internet to communicate with friends was associated with a lower risk of bullying in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We can hypothesize that the preference for online image-ma king is sometimes due to problematic image-making offline, or due to the choice of an online image that is socially undesirable and could lead to poorer adjustment. Supporting this hypothesis is the fact that youth preference for online self-presentation is associated with a less stable sense of self (Fullwood et al, 2016), although longitudinally it could lead to better self-esteem (yang & Brown, 2016). It could be that (both in youth and adults) by becoming the main sphere where person is able to create and share his preferred meaning with others, the Internet becomes a highly unique place, thus increasing the person's vulnerability to Internet addiction.…”
Section: Discussionmentioning
confidence: 99%